Bridging theory and practice: the role of experiential learning in deepening understanding of industrial relations - Abd Samad, Suhaimi; Abd Hamid, Siti Nur Fathanah; Abdul Halim, Syahrina Adliana; Mahmud, Mohammad Bastyian (Faculty of Administrative Science and Policy Studies, 2025)
This study explores the implementation of role play as an experiential learning tool in the Principles of Industrial Relations (PAD363) course at Universiti Teknologi MARA. The objective is to evaluate how role play enhances students' understanding of industrial relations concepts while fostering problem solving, communication, and collaborative skills. The methodology involves task-based learning where students, in groups of 7-8, develop and perform role play scenarios reflecting real-world industrial issues, such as labour disputes and collective bargaining. Data were collected through video recordings of the role plays and reflective essays, which were analysed to assess the students’ learning experiences. Findings indicate that role play effectively bridges the gap between theoretical knowledge and practical application, enabling students to grasp complex industrial relations processes more thoroughly. Students reported increased comprehension, improved teamwork, and the acquisition of new skills like acting and video editing. Furthermore, the activity enhanced interpersonal relationships, creating a supportive learning environment. This study underscores the value of experiential learning in industrial relations education, suggesting that role play can serve as a dynamic and engaging pedagogical approach to reinforce both academic understanding and real-world competencies.